ANALYSING THE IMPACT OF DIGITAL INFRASTRUCTURE INVESTMENT ON MSME GROWTH IN DISADVANTAGED AREAS - Dwi Apriyanti Kumalasari; Al-Amin (Adisam Publisher, 2025)
Digital infrastructure investment has great potential to boost the growth of Micro, Small, and Medium Enterprises (MSMEs) in disadvantaged areas. This study aims to analyse the impact of digital infrastructure development on improving market access, operational efficiency, and competitiveness of MSMEs in lagging regions. The results of the analysis show that improved internet access, digitalisation of business services, and the development of digital training centres can provide opportunities for MSMEs to grow significantly. However, a number of challenges such as low digital literacy, limited capital, and policies that are not yet fully supportive hinder the optimisation of the benefits of these investments. Therefore, a holistic strategy consisting of policy support, digital education, and business ecosystem strengthening is needed to maximise the positive impact of digital infrastructure. These findings emphasise the important role of digital investment in reducing economic disparities in underdeveloped regions and strengthening the position of MSMEs as sustainable drivers of the local economy.